2017
DOI: 10.1080/02642069.2017.1351550
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual underpinnings for transformative research in a service ecosystems context to resolve social issues – framework foundations and extensions

Abstract: A number of services within society are designed to improve the wellbeing of its members and transform lives. Some services focus on protection and support of vulnerable members of society, for example, those suffering the effects of drug use, mental health conditions, violence, or poverty. Clients of such social services may also come from minority or marginalised cultural backgrounds. Typically, social services aim to reduce disparities and enhance individual and population wellbeing. A major challenge for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Transformative Service Research (TSR) proposes a coherent approach to framing Airbnb research. It identifies and models the determinants of well‐being that services are meant to achieve for communities and formalizes service theory at the middle level of theory development (Anderson, Ostrom, & Bitner, 2011; Blocker & Barrios, 2015; Finsterwalder et al, 2017). TSR has conceptual parallels with the service‐dominant logic (S‐D logic; Vargo & Lusch, 2008).…”
Section: Literature Review: Underpinning Constructsmentioning
confidence: 99%
“…Transformative Service Research (TSR) proposes a coherent approach to framing Airbnb research. It identifies and models the determinants of well‐being that services are meant to achieve for communities and formalizes service theory at the middle level of theory development (Anderson, Ostrom, & Bitner, 2011; Blocker & Barrios, 2015; Finsterwalder et al, 2017). TSR has conceptual parallels with the service‐dominant logic (S‐D logic; Vargo & Lusch, 2008).…”
Section: Literature Review: Underpinning Constructsmentioning
confidence: 99%
“…Second, this study contributes to TSR by focusing on socially and emotionally isolated people (Rosenbaum, 2008). TSR emphasizes the well-being of individuals and society at large (Finsterwalder et al, 2017;Kuppelwieser and Finsterwalder, 2016) where loneliness is regarded an indicator of well-being (Cacioppo and Patrick, 2008). Therefore, the developed integrative framework introduces the roles of personal assistant, relational peer and intimate buddy as three potential roles that companion robots can fulfill to mitigate feelings of loneliness (i.e.…”
Section: Contributions To Service Researchmentioning
confidence: 99%
“…These systems can be labeled as social ecosystems (Fisk et al 2016 ). This social service ecosystem comprises a complex relational structure of organizations, institutions, and relationships through which social services are funded, coordinated, and delivered (Finsterwalder et al 2017 ).…”
Section: Literaturementioning
confidence: 99%
“…Service research has increasingly found its way into the domain of social services to protect and support against vulnerability (e.g., Fisk et al 2016 ). Social services comprise a wide spectrum of programs developed by the different stakeholders of a territory for collectives that need assistance or address complex societal outbreaks (Finsterwalder et al 2017 ). Within an increased demand for social services due to an unexpected shock, the development of networks between public, non-profit and private organizations providing essential social services seems crucial to produce collective and cooperative actions (Sanzo et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%